Analysis Perception of Teacher's Physical Education Model Based on Creativity and Indenpendency - Idris Moh Latar; Ema Rummahlewang (Peneliti.net, 2020)
This study aims to handle teacher perceptions of physical education models based on creativity and independence. The sample in this study were 24 elementary school teachers in Ambon city. The methodology used is research and development research with the dissemination stage. Data is taken by giving questionnaire to Physical Education teachers. The results showed that the teacher's perception of the model with a score of 404 or 15 people strongly agreed, 236 as many as 6 people agreed, 74 or 2 people disagreed, and 1 person disagreed. Based on the results of this study it can be concluded that the teacher's perception of the model is very good, and the effective model is used in the learning process